Manejo del dolor dental y su reagudización en la población mayor de 18 años de la parroquia De Valle Hermoso cantón Las Lajas de la provincia de El Oro, 2016 - Celi Poma, Doris María (2016)
Tooth pain is one of the most annoying pain that occurs in humans, in which the patient tends to calm him immediately, now traditional medicines with drugs are of the highest use due to the economic reality in which the country finds itself. This research was conducted in the population over 18 years in Valle Hermoso parish Canton Las Lajas in the province of El Oro, 2016. The same that aimed to know the management of dental pain and heightening, surveying 208 people over 18 years, then the tabulation and analysis of the data was performed and found to be most prevalent management to control pain is dental use of traditional medicine (63%); compared with (36%) than self-medicate and (1%) receive professional care, likewise the (65%) had acute exacerbation after treatment employed. Keywords: management, dental pain, heightening, traditional medicine